Intervensi Pemerintah Dalam Perjanjian Jual Beli Tanah Dan/Atau Bangunan Melalui PP No 34 Tahun 2016 - Ayu Dwi Novitasari (Darma Cendika Catholic University, 2018)
Tax is the largest income for the state, but through Government Regulation no. 34 Year 2016 by lowering the tax for the seller does not necessarily relieve the taxation charge on the sector of sale and purchase of land and / or building, the sale and purchase of land and / or building is an agreement between the parties to buy immovable property (land and / or building ). As a form of freedom of contract can the government restrict and intervene the agreement through its legal products. For that reason, the research is conducted with normative juridical because it aims to know the limits of government to intervene on the sale and purchase agreement of land and/or building through Government Regulation 34 of 2016 which is inconsistent with BPHTB Law and knows the limits of freedom of contract in the land and / or building purchase agreement on Government Regulation no. 34 Year 2016. Because as a form of implementation of the principle of self assessment then the Government serves as a counterweight of freedom of contract if there is a market failure to avoid natural monopoly.